Covid-19 and Low Platelet Count-A Relationship (Indian Journal of Public Health Research & Development, 2021)
Background: Easily accessible, inexpensive, and widely used laboratory tests that demonstrate the severityof COVID-19 are important. Therefore, in this study, we aimed to investigate the relationship betweenmortality in COVID-19 and platelet count, Mean Platelet Volume (MPV), and platelet distribution width.Method: In total, 100 COVID-19 patients were included in this study. The patients were divided into twogroups. Patients with room air oxygen saturation < 90% were considered as severe COVID-19, and patientswith ?90% were considered moderate COVID-19. Patient medical records and the electronic patient datamonitoring system were examined retrospectively. Analyses were performed using the SPSS statisticalsoftware. A p-value
Keywords: Coronavirus Infections; Blood Platelets; Mean platelet volume; Mortality